A hidden gem from Northeastern Brazil: A new species of Metaphotina Piza, 1964 (Mantodea, Acontistidae) ecologically linked to the Caatinga - Ferraz, Bernardo R.; Souza-Dias, Pedro G.b.; Rivera, Julio (Zootaxa, 2023)
A new species of praying mantis, Metaphotina austri sp. n., is described from the Caatinga biome in Brazil. The species can be easily distinguished from its congeners by its small body size and diagnostic characters found on the head, wings, and male genitalia. Distributional data compiled from specimen labels, historical literature, and the citizen science platform iNaturalist showed that M. austri sp. n. is mainly associated with the northernmost and driest region of the Caatinga, known as the “Depressão Sertaneja Setentrional.” Ecological and geographical data about the new species, as well as comments on the diversity of Mantodea in the Caatinga, are provided, highlighting the importance of crowdsourced data for a more comprehensive understanding of praying mantis species’ distribution and their natural history.